THE INFLUENCE OF SOCIAL MEDIA ON FAMILY COMMUNICATION PATTERNS IN THE DIGITAL ERA - Marbun, Lathifah Amri; Nasution, Dienaya Rahesya (OPINI: Journal of Communication and Social Science, 2024)
The purpose of this study is to examine the influence of social media on family communication patterns in the digital era. This research employs a quantitative approach through a literature review, involving data collection from scholarly sources and previous studies. The development of information technology, particularly social media, has helped people work and communicate more effectively. Social media enables interaction and social relationships, and today almost all human activities are supported by digital technology. Individuals engage in digital exchanges through digital symbols. Advances in technology and communication media have also transformed family interactions as well as other sectors such as the economy, politics, education, and culture. The physical dimension of family life has increasingly been replaced by virtual realities, and family interactions in the digital era depend heavily on information technology. Therefore, this study seeks to test the impact of social media on family communication patterns in the digital era. The findings indicate that social media shapes digital family communication patterns by making it easier for every age group within the family to use social media. In addition, when children are at home, parents are not able to fully control the flow of information received by their children. Communication between family members particularly between parents and children tends to be less smooth and unbalanced, which also encourages individualistic behavior as family members become preoccupied with their mobile phones.